CGIAR Initiative on Nature-Positive Solutions: CIMMYT final report - Odjo, Sylvanus; González Regalado, Jessica; Romero Parilla, Nestor; Bolaños Vargas, Janeth; Goulet, Frederic; González Reyes, Gabriela; Verhulst, Nele (International Maize and Wheat Improvement Center, 2024)
The Nature+ initiative was launched in 2022 as part of the OneCGIAR strategy to develop and implement solutions that support local food systems and livelihoods equitably while ensuring that agriculture contributes positively to the planet's ecosystems. CIMMYT participated in this initiative with a focus on Colombia and Burkina Faso through the "Conserve," "Manage," and "Recycle" work packages. Activities implemented included different diagnostics in the targeted countries (farmers typologies, stakeholders mapping, social network mapping of informal seed systems) in these regions through a nature-positive approach to understand the local contexts. Additional activities included co-designing solutions to address challenges identified by farmers and providing training on agrobiodiversity management. Overall, the CIMMYT team engaged with thousands of farmers and 36 different stakeholders (34 in Colombia and 2 in Burkina Faso) through 72 events, meetings, workshops and training. Throughout he initiative, farmers received training in improved seed postharvest practices, ensuring the preservation of native maize and other crops. A total of 782 farmers (58% of women) participated in seed storage training. In addition, 11 community seed banks in Colombia were also strengthened with different equipment (moisture meters, dryers, sieves, airtight containers), providing local farmers with tools and knowledge to preserve agrobiodiversity. Smallholders' access to niche markets was part of the activities implemented, with workshops and matchmaking events to help bridge the gap between farmers and buyers and address challenges such as inconsistent supply, postharvest losses, and intermediaries dependence. The project also fostered collaboration with government institutions, including the Colombian Ministry of Agriculture, to create favorable policies for the promotion of bioinputs and sustainable farming practices. Within the Multifunctional Landscape Science Program, CIMMYT, in collaboration with the other centers, will focus on expanding these efforts, with an emphasis on participatory varietal selection, business models to connect farmers with market opportunities, and women empowerment for biodiversity conservation. Efforts toward strengthening the seed systems for landraces will also continue, promoting biodiversity conservation and agroecological pest management practices. The collaboration with governmental institutions will continue to help co-design policies that support the production of bioinputs and biofactories and their accessibility to smallholder farmers, helping to create more sustainable farming systems across Colombia and Burkina Faso.